Crude estimates of prescription opioid-related misuse and use disorder populations towards informing intervention system need in Canada. (1st August 2018) - Fischer, Benedikt; Varatharajan, Thepikaa; Shield, Kevin; Rehm, Jürgen; Jones, Wayne
Highlights: Estimates for populations with PO misuse and use disorder in Canada do not exist. Populations were simulation-estimated based on survey and systematic review data. Point estimates (2008) for PO misuse: 5.1% (1, 408, 223); PO disorder: 1.9% (525, 100). Point estimates (2015) for PO misuse: 3.1% (930, 297); PO disorder: 1.2% (346, 890). PO-related risk populations are assumed to exceed existing intervention resources. Abstract: Background: Numerous interventions aimed at addressing the Canadian 'opioid crisis' have been implemented. However, no empirical estimaes of the number of people with problematic prescription opioid (PO) use exist to inform and guide intervention system needs. Methods: The annual numbers of Canadian adults (≥ 15 years) with PO misuse and/or use disorders ('addiction') were estimated by combining data on the prevalence and associated 95% Confidence Intervals (CIs) of PO use in the Canadian population, obtained from national surveys, with PO misuse and use disorders transition probabilities, obtained from high-quality studies in recent meta-analyses. Uncertainty Intervals (UI) were estimated using Monte Carlo simulations. Results: Population estimates of PO use were highest in 2008, with 5, 967, 046 (95% CI: 5, 635, 543–6, 326, 173) people using POs (representing 21.6% of adults), and lowest in 2015, with 3, 941, 935 (95% CI: 3, 580, 842–4, 272, 937) people using POs (13.1%). Furthermore, PO misuse and use disorders were highest in 2008, with 1, 408, 223 (95% UI: 878, 686–1, 951, 211; 5.1% of adults) and 525, 100 (95% UI 258, 288–801, 472; 1.9%) people with PO misuse and use disorders respectively. These numbers declined to 930, 297 (95% UI: 576, 083–1, 295, 310; 3.1% of adults) and 346, 890 (95% UI: 168, 310–532, 941; 1.2%) people with PO misuse and use disorders, respectively, in 2015. Conclusion: While seemingly declining over-time, the crude population estimates for problematic PO use were high, likely outweighing current intervention capacities. Furthermore, these estimates do not account for the delay of onset and duration of PO misuse and disorders. Thus, more rigorous problem population estimates should be generated to guide interventions.